2019
DOI: 10.1177/0009922819850476
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyurea Initiation Among Children With Sickle Cell Anemia

Abstract: This study assesses characteristics of children with sickle cell anemia associated with hydroxyurea initiation. Medicaid administrative claims from 6 states (2005-2012) were used to identify children with sickle cell anemia enrolled in Medicaid for ≥2 years. Hydroxyurea use was defined as >30 days’ supply of filled prescriptions. Children were classified as initiators (no use in year 1; use in year 2) or nonusers (no use in either year). Logistic regression was used to estimate associations between initiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 55 publications
(71 reference statements)
0
11
0
Order By: Relevance
“…It is also remarkable that our patients who got hydroxyurea experienced lower mental HRQoL compared to those patients who did not. Despite documented benefits of hydroxyurea for pediatrics and young adults with SCD [ 47 , 48 ], Ceveher et al [ 49 ] proposed that quality of life and compliance of SCD patients might be low due to not sufficiently effective hydroxyurea therapy, comorbidities, concomitant medication use, and side effects. This issue can be explained in part by the previous patients' perceptions of treatment benefits versus risks, and their disease severity.…”
Section: Discussionmentioning
confidence: 99%
“…It is also remarkable that our patients who got hydroxyurea experienced lower mental HRQoL compared to those patients who did not. Despite documented benefits of hydroxyurea for pediatrics and young adults with SCD [ 47 , 48 ], Ceveher et al [ 49 ] proposed that quality of life and compliance of SCD patients might be low due to not sufficiently effective hydroxyurea therapy, comorbidities, concomitant medication use, and side effects. This issue can be explained in part by the previous patients' perceptions of treatment benefits versus risks, and their disease severity.…”
Section: Discussionmentioning
confidence: 99%
“…Pain crises are associated with substantially lower quality of life, as well as inadequate sleep, increased school absences, chronic depression, and impaired peer relationships 7,32–35 . Although hydroxyurea has been recommended, previous studies have indicated both initiation and adherence are low 13,20,21,23 . Our results suggest that without sustained adherence after initiation, improvements in VOC and ACS outcomes will be hampered.…”
Section: Discussionmentioning
confidence: 70%
“…7,[32][33][34][35] Although hydroxyurea has been recommended, previous studies have indicated both initiation and adherence are low. 13,20,21,23 Our results suggest that without sustained adherence after initiation, improvements in VOC and ACS outcomes will be hampered.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations